Asenapine: an atypical antipsychotic with atypical formulations - Meghan Musselman; Justin Faden; Leslie Citrome (Therapeutic Advances in Psychopharmacology, 2021)
Asenapine is a second-generation (atypical) antipsychotic medication not available in a pill that can be swallowed; rather, it is commercialized in sublingual and transdermal formulations. This is a consequence of extensive first-pass metabolism if ingested. The sublingual formulation is approved in many jurisdictions for the treatment of schizophrenia and manic or mixed episodes associated with bipolar I disorder and is available generically. The efficacy profile is well characterized in a number of clinical trials, including an off-label use for the management of agitation. Obstacles to its use include food and drink restrictions, twice-daily dosing and adverse effects such as dysgeusia (distorted, altered, or unpleasant taste) and oral hypoesthesia (numbness). Transdermal asenapine was approved by the US Food and Drug Administration in 2019 for the treatment of schizophrenia in adults. Efficacy was established in a registrational study examining acutely ill inpatients with schizophrenia. The patch needs to changed once daily. Obstacles to its use include the potential for skin reactions such as erythema and pruritis, and being a branded product, it is more costly than other options. This is a narrative review of the chemistry and pharmacokinetics/pharmacodynamics of asenapine, as well as summarizing the efficacy and tolerability of both sublingual and transdermal asenapine, and its possible place in treatment.